Réponses

Meilleure réponse !
2013-11-23T15:31:02+01:00
A) A = (2x+1)(5x-3)-(2x+1)
A = 2x*5x +2x*-3 + 5x-3 -2x-1  (* est multiplié par)
A = 10x² -6x  +5x -2x -4
A = 10x² -3x-4

b) x= -1
A = 10x²-3x-4
A = 10*(-1)² -3*-1 -4
A = 10+3-4
A = 9

x=1/3
A = 10x²-3x-4
A = 10(1/3)² -3*1/3 - 4
A = 10/9 -4
A = 10/9 -36/9
A = 26/9

dans a) 2x*5x = 2*5*x*x =10*x*x = 10x²
dans b) je remplace x par -1 et x² par (-1)² = 1
je remplace x par 1/3 et x² par (1/3)² =1²/3² = 1/9
Est-ce que c'est plus clair comme ça ?
oui merci
De rine:)
Pardon, de rien :)